Postinterventional pain and complications of sonographically guided interventions in the liver and pancreas - Lindner, A.; Frieser, M.; Heide, R.; Wildner, D.; Neurath, Markus; Dauth, W.; Bernatik, T.; Strobel, Deike (Ultraschall in der Medizin, 2014)
Sonographically guided interventions in abdominal organs are routine procedures with rare severe complications. However, potential patient discomfort or pain is frequently not addressed in the literature.In a prospective 1-year study, the peri- and postinterventional pain of patients undergoing sonographically guided punctures of the liver and pancreas was analyzed. Data acquisition was done with a standardized questionnaire. This included three numeric rating scales (NRS) ranging from "0" to "10" to be answered at puncture and 1 hour and 4 hours later. Data concerning complications and administered analgesic medication was acquired from the patients' charts.223/274 patients could be analyzed (83 %). 91 women (40.8 %) and 132 men (59.2 %) were included. The mean age was 56.0 yrs. Overall the average level of pain was 2.98 at puncture, 1.21 after 1 hour and 0.71 after 4 hours. In patients with diagnostic biopsies, the pain levels were 3.37(0 h)/1.33(1 h)/0.71(4 h) for liver parenchyma, 2.64(0 h)/0.95(1 h)/0.65(4 h) for focal liver lesions and 3.1(0 h)/1.9(1 h)/1.1(4 h) for pancreatic punctures. The pain levels at therapeutic interventions were 3.00(0 h)/2.00(1 h)/0.50(4 h). Female and younger (< 50 yrs) patients had statistically significantly more pain at puncture and 1 hour postintervention. Only minor complications occurred (0.9 %).Severe pain after sonographically guided interventions is rare. Most patients suffer only from mild pain postinterventionally.
EVALuna2:1874